Educating gender equity through non-competitive cooperative motor games: Transforming stereotypes and socio-affective dynamics - Carlos Mallén-Lacambra; Miguel Pic; Pere Lavega-Burgués; Zhaira Ben-Chaabâne (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Non-competitive cooperative motor games hold the potential to educate gender equity from a relational perspective. These motor games present educational relational challenges where different genders interact for mutual benefit. Such interactions generate emotional well-being, enhance socio-affective relationships, and promote feminized motor conducts that potentially perform gender hegemonies and reduce gender stereotypes. This study, grounded in the ethics of care and motor praxeology, explored the effects of non-competitive cooperative motor games on group and cross-gender socio-affective rejections, gender stereotypes and emotional well-being, along with the mediation effects of these interconnected variables. Researchers conducted a quasi-experimental study where 11 participants (Mage = 11.16; SD = 1.35) from a summer sports camp played non-competitive cooperative motor games. The study employed sociometric questionnaires, emotional questionnaires (PANAS-C) and gender stereotype questionnaires (NATGEN). Data were analyzed using inferential and descriptive statistical techniques, social network analysis and mediation analysis. Results revealed the effectiveness of non-competitive cooperative motor games in reducing cross-gender rejections among girls, maintaining low group rejections, promoting emotional well-being and reducing gender stereotypes. Mediation analysis showed that gender stereotypes and positive emotions act as a protective barrier against group rejection. This study presents an innovative educational perspective that combines the scientific foundations of motor praxeology with the theoretical bases of the ethics of care. The research provides teachers and researchers with a practical pedagogical tool based on non-competitive cooperative motor games. These games are designed to enhance gender equity, promote emotional well-being, and reduce gender-based rejection and stereotypes.